PENILAIAN INFRASTRUKTUR JALAN DESA BERDASARKAN INDEKS DESA MEMBANGUN (IDM) KABUPATEN WONOGIRI - Ristanto, Iwan; Firdausi, Annisa Azhar (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2024)
Developing Village Index (IDM) is an indicator tool developed based on the concept of the village development framework. This study examines the interaction between the use of Dana Desa (DD) for building village roads, bridges, and drainage systems. In Tirtomoyo District, IDM categorizes villages into two statuses: Developing Villages and Advanced Villages. The study analyzes how these statuses relate to village infrastructure development. The type of infrastructure factor (Factor 1) and the village status factor (IDM) (Factor 2) both have sig values. = 0.000 < ???? = 0.050 so it has an influential relationship with assessments at the planning, implementation and supervision stages of village development. The interaction between Factor 1 and Factor 2 has a sig value. = 0.000 < ???? = 0.050 so that these two factors influence each other on the assessment at the planning, implementation, and supervision stages of village development. The results of the assessment at the planning (RAB) and monitoring stages, developed villages have a higher assessment on 2 infrastructure (roads and bridges) and a smaller value on drainage infrastructure but the difference is not much compared to developing villages, but at the village implementation stage developed villages have a higher assessment of 3 infrastructure (drainage, roads, and bridges) compared to developing villages.